Physical, chemical, microbiological and sensory characteristics of a probiotic beverage produced from different mixtures of cow's milk and soy beverage by Lactobacillus acidophilus La5 and yoghurt culture - Šertović, Edina; Sarić, Zlatan; Barać, Miroljub B.; Barukčić, Irena; Kostić, Aleksandar; Božanić, Rajka (2019)
The aim of this paper is to determine nutritive, functional, microbiological and sensory properties of probiotic beverages produced from different volume ratios of cow's milk and soy beverage (25:75, 50:50 and 75:25). Pure cow’s milk and soy beverage served as control samples. Fermentation was performed at 43 °C by a combined culture consisting of the probiotic strain Lactobacillus acidophilus La5 and yoghurt culture. Viable counts of La5 strain in the produced beverages ranged from 7.52 to 8.20 log CFU/mL, which is above the probiotic minimum (106 CFU/mL). Lactic acid was the most prevalent organic acid in all samples (660.1 to 1003.0 mg/100 mL). The fatty acid profiles of fermented beverages were as follows: the mass fraction of saturated fatty acids was 22.2–82.7 %, of unsaturated fatty acids 22.3–77.8 % and of polyunsaturated fatty acids 15.5–65.9 %. The main soy sugars were transformed well (80 % stachyose and 50 % raffinose conversion) into lactic acid during fermentation. Functional probiotic beverages were successfully produced from different volume ratios of cow's milk and soy beverage by L. acidophilus La5 and yoghurt culture. Mixing cow's milk with soy beverage significantly improved the sensory properties of the product, especially its smell, taste and colour. The acceptability test showed good acceptance by potential consumers of all fermented beverage samples except for the sample made from 100 % soy beverage. In the end, the obtained results represent a good basis for optimisation of the ideal volume ratios of cow's milk and soy beverage for production of fermented beverages characterised by good viability of probiotic bacteria as well as by good functional, nutritive and sensory characteristics.
Svrha je ovoga rada bila odrediti hranjiva, funkcionalna, mikrobiološka i senzorska svojstva probiotičkih napitaka proizvedenih od smjese kravljeg mlijeka i sojinog napitka u različitim omjerima (25:75, 50:50 i 75:25). Kao kontrolni uzorci korišteni su kravlje mlijeko i sojin napitak. Fermentacija je provedena na 43 °C s pomoću mješovite kulture sastavljene od klasične jogurtne kulture i probiotičkog soja Lactobacillus acidophilus La5. Broj živih stanica soja La5 kretao se između 7,52 i 8,20 log CFU u mL proizvedenog napitka, što je iznad probiotičkog minimuma (106 CFU/mL). Mliječna kiselina je bila najzastupljenija organska kiselina u svim uzorcima (660,1 do 1003,0 mg/100 mL). U fermentiranim napicima bilo je 22,2-82,7 % (m/m) zasićenih i 22,3-77,8 % (m/m) nezasićenih masnih kiselina, od čega njih 15,5-65,9 % višestruko nezasićenih. Glavni šećeri iz sojinog napitka većim su dijelom fermentirali u mliječnu kiselinu (stupanj konverzije: 80 % stahioza, 50 % rafinoza). Funkcionalni probiotički napici uspješno su proizvedeni iz smjese kravljeg mlijeka i sojinog napitka u različitim omjerima fermentacijom s pomoću jogurtne kulture i L. acidophilus La5. Dodavanjem sojinog napitka kravljem mlijeku znatno su poboljšana senzorska svojstva krajnjeg proizvoda, pogotovo miris, okus i boja. Ispitivanjem je utvrđeno da potencijalni potrošači dobro prihvaćaju sve napitke, osim fermentiranog sojinog napitka.
Bibliografija: 48 jed.
Summary ; Sažetak.
Keywords: Kravlje mlijeko -- Sojin napitak -- Lactobacillus acidophilus -- Probiotici -- Fermentacija